2016
DOI: 10.1016/j.neuron.2016.10.060
|View full text |Cite|
|
Sign up to set email alerts
|

The Mammalian-Specific Protein Armcx1 Regulates Mitochondrial Transport during Axon Regeneration

Abstract: Mitochondrial transport is crucial for neuronal and axonal physiology. However, whether and how it impacts neuronal injury responses, such as neuronal survival and axon regeneration, remain largely unknown. In an established mouse model with robust axon regeneration, we show that Armcx1, a mammalian-specific gene encoding a mitochondria-localized protein, is up-regulated after axotomy in this high regeneration condition. Armcx1 overexpression enhances mitochondrial transport in adult retinal ganglion cells (RG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 44 publications
2
147
0
Order By: Relevance
“…For example, ARMCX1 is a mammalian-specific gene that controls mitochondrial transport during neuronal repair 203 . Increased mitochondrial transport to injured axons is required for regeneration 203,204 , and CSPGs can prevent mitochondria from localizing to the growth cone 205 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ARMCX1 is a mammalian-specific gene that controls mitochondrial transport during neuronal repair 203 . Increased mitochondrial transport to injured axons is required for regeneration 203,204 , and CSPGs can prevent mitochondria from localizing to the growth cone 205 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, ARMCX1 is a mammalian-specific gene that controls mitochondrial transport during neuronal repair 203 . Increased mitochondrial transport to injured axons is required for regeneration 203,204 , and CSPGs can prevent mitochondria from localizing to the growth cone 205 . There are also human-specific mRNA splice variants and human-specific genes in the nervous system that may play a role in the regenerative response 206208 .…”
Section: Discussionmentioning
confidence: 99%
“…Parallel work in invertebrate and rodent model organisms has shown that, on the one hand, mitochondria are likely to influence axonal growth patterns during development (Courchet et al, 2013; Spillane et al, 2013), but also after axotomy during regeneration (Cartoni et al, 2016; Han et al, 2016; Knowlton et al, 2017; Zhou et al, 2016). In this case, most data point towards a classical bioenergetic role, where axonal mitochondria at or near the growing axon tip are simply needed for sustained axon growth.…”
Section: Mitostatic Diseasesmentioning
confidence: 99%
“…Disorders that more broadly affect axonal transport, such as tauopathies and SOD1 mutations, may include phenotypes with a significant mitochondrial etiology (De Vos et al, 2008; Millecamps and Julien, 2013). More recently changes in mitostatic processes also have been described during neuroinflammation (Sadeghian et al, 2016; Sorbara et al, 2014; Witte et al, 2014) and after neurotrauma (Cartoni et al, 2016; Han et al, 2016; Sheng, 2017; Zhou et al, 2016). Such links to pathology rightly spur interest in understanding mitostasis.…”
Section: Introduction: Mitostasis In Neuronsmentioning
confidence: 99%
“…Depolarizing mitochondria does not increase the rate of Wallerian degeneration in superior cervical ganglion axons in vitro , indicating that degeneration-associated Ca ++ increases are extra-mitochondrial (Loreto et al, 2015). Axon regeneration, quite separate from degeneration, in mouse RGC axons (Cartoni et al, 2016) and C. elegans nerve cord axons (Han et al, 2016), does require mitochondria.…”
Section: Energy In Axonsmentioning
confidence: 99%